MAKNA INTERPERSONAL DEIKSIS DALAM NOVEL CATATAN JUANG KARYA FIERSA BESARI - Amriyadi Anwar; Muhammad Rapi; Aswati Asri (Universitas Negeri Makassar, 2022)
The Interpersonal Meaning of Deixis in the Novel Notes Juang by Fiersa Besari. This study aims to identify and describe the deixis contained in the novel Notes Juang by Fiersa Besari. This research is a qualitative research. The data in this study are in the form of words and phrases. The data source of this research is the novel Notes Juang by Fiersa Besari published by mediakita in 2017. In this study, the researcher first reads the novel that was used as the data source and then recorded and classified the data according to the problem formulation and theory used. The results of the study stated that the novel Notes Juang by Fiersa Besari contains three types of deixis, including person deixis, place/space deixis, and time deixis. The three types of deixis are further divided into several forms based on the object or referent. This research is dominated by persona deixis because the story line basically tells a character who is often referred to as